Adaptor CAR platform: next generation of T Cell-Based cancer ommunotherapy - Arndt, Claudia; Faßlrinner, Frederick; Loureiro, Liliana R.; Koristka, Stefanie; Feldmann, Anja; Bachmann, Michael (Cancers, 2020)
The success of conventional chimeric antigen receptor (CAR) therapy in the treatment of refractory hematologic malignancies has triggered the development of novel exciting experimental CAR technologies. Among them, adaptor CAR platforms have received much attention. They combine the flexibility and controllability of recombinant antibodies with the power of CARs. Due to their modular design, adaptor CAR systems propose answers to the central problems of conventional CAR therapy, such as safety and antigen escape. This review provides an overview on the different adaptor CAR platforms available, discusses the possibilities and challenges of adaptor CAR therapy, and summarizes the first clinical experiences.
Gesehen am 30.09.2020